Sustainability of extensive livestock production systems: the challenge of PA technologies - Serrano, João (2020)
In the extensive livestock production systems of southern Portugal the basis of animal feed is provided by biodiverse pastures, complemented by the availability of acorns in the winter period. Since the turn of the new millennium, greater recognition of the importance of pastures and grasslands in conserving soil, promoting biodiversity, stabilizing farming communities, and providing a wealth of natural ecosystem services has led to renewed interest in the dynamics of grasslands function. This important agro-silvo-pastoral ecosystem, known as Montado, is characterized by a high complexity resulting from the interactions between climate, soil, pasture, trees, and animals. Its sustainability depends on its capacity to improve soil fertility, to increase pasture productivity and the rational use of production factors (especially soil amendment or fertilization) and to promote dynamic grazing (livestock numbers and time of grazing in each plot). In order to achieve these objectives, it is essential to calibrate and validate expeditious monitoring tools that provide information to support decision making. This work presents the results of a study carried out between 2015 and 2019 on a 4.0 ha experimental field located at Mitra farm (plot “ECO-SPAA”). Proximal sensors were used to monitor the electrical conductivity and soil resistance, the productivity and quality of pasture, the leaf area index of trees and the animal grazing preferences. The interest of remote sensing from satellite images was also evaluated and demonstrated to monitor pasture quality and produce a warning system for feed supplementation needs. The results showed the potential of technologies associated with precision agriculture (PA). These tools provide a better understanding of the Montado ecosystem what allows the optimization of the herbaceous stratum and the dynamic management of grazing in a holistic and sustainable form.